Authorial Presence in French and English: “Pronoun + Verb” Patterns in Biology and Medicine Research Articles - Laura M. Hartwell; Marie-Paule Jacques (Discours)
Certain subjective qualities of scientific research articles are exposed when authors refer to themselves through various means including pronoun use. Drawing upon the online bilingual “Scientext” corpus, we compare personal pronoun and syntactically linked verb constructions within 180 published articles in English and French in the fields of medicine and biology. This study found that overall pronoun frequency was significantly higher (χ2 = 69.45, df = 1, p